Genome-resolved metagenomics provides insights into the microbial-mediated sulfur and nitrogen cycling in temperate seagrass meadows - Liu, Pengyuan; Zou, Songbao; Zhang, Haikun; Liu, Qing; Song, Zenglei; Huang, Yanyan; Hu, Xiaoke (Frontiers in Marine Science, 2023)
The presence of seagrasses facilitates numerous microbial-mediated biogeochemical cycles, with sulfur- and nitrogen-cycling microorganisms playing crucial roles as regulators. Despite efforts to comprehend the diversity of microbes in seagrass ecosystems, the metabolic functions of these benthic microorganisms in seagrass sediments remain largely unknown. Using metagenomics, we provide insights into the sulfur- and nitrogen-cycling pathways and key metabolic capacities of microorganisms in both Z. japonica-colonized and unvegetated sediments over a seasonal period. Taxonomic analysis of N and S cycling genes revealed that δ- and γ- proteobacteria dominated the benthic sulfate-reducing bacteria, while α- and γ-proteobacteria played a significant role in the sulfur-oxidation processes. The proteobacterial lineages were also major contributors to the benthic nitrogen cycling. However, at a finer taxonomic resolution, microbial participants in different processes were observed to be highly diverse and mainly driven by environmental factors such as temperature and salinity. The gene pools of sulfur and nitrogen cycles in the seagrass sediments were dominated by genes involved in sulfide oxidation (fccA) and hydroxylamine oxidation (hao), respectively. Seagrass colonization elevated the relative abundance of genes responsible for sulfite production (phsC), hydroxylamine oxidation (hao), and nitrogen fixation (nifK), but suppressed sulfur oxidation (soxXYZ) and denitrification (nosZ and nirS). The prevalence of proteobacterial lineages functioned with versatile capabilities in both sulfur and nitrogen cycles in seagrass ecosystems, highlighting tight couplings between these processes, which was further supported by the recovery of 83 metagenome-assembled genomes (MAGs). These findings broaden our understanding of the biogeochemical processes that are mediated by microorganisms in seagrass ecosystems.